2019
DOI: 10.2147/cia.s201873
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prediction of chemotherapy adverse reactions and mortality in older patients with primary lung cancer through frailty index based on routine laboratory data</p>

Abstract: Objectives To assess the role of a pre-chemotherapy frailty index based on routine laboratory data in predicting mortality and chemotherapy adverse reactions among older patients with primary lung cancer. Design Retrospective cohort study Setting West China Hospital, Chengdu, China Participants We included patients aged ≥60 years with primary lung cancer receiving the first course of chemotherapy. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…In humans, FIs based on the clinical data of the patient 11 and on laboratory evaluations (mainly blood tests) have been developed 8,1820 . An FI combining both clinical and laboratory findings has been developed in mice 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, FIs based on the clinical data of the patient 11 and on laboratory evaluations (mainly blood tests) have been developed 8,1820 . An FI combining both clinical and laboratory findings has been developed in mice 21 .…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies were hospital-based registry cohort studies. A total of 3,921 lung cancer patients involved in these seven studies received different treatments, surgery in two (17,21), radiotherapy in two (14,15), chemotherapy in two (22), unreported in one. Three of these included studies classified patients as prefrail and frail, and one classified patients as mild, moderate and severe frailty.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Two included studies explored the role of prefrailty in predicting the risks of overall mortality in patients with lung cancer (22,23). Figure 2B showed forest plots, which showed the HR of the association between prefrailty and overall mortality.…”
Section: Overall Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that aging increased the risk of frailty (26)(27)(28), since the escalating incidence of frailty with old age was associated with the mounting physiological dysregulation with ageing in a nonlinear manner. When frailty is present, stress responses are highly dysregulated and there is high vulnerability to adverse outcomes (25,29,30).…”
Section: Discussionmentioning
confidence: 99%